The Competition for the Sacred Body: The Problem and Potential of Liturgical Dance for the Roman Catholic Church - Vloebergs, Sander 1992- (2025)
While dance research is an established field, liturgical dance as a research practice is still emerging. This paper aims to lay the groundwork for this new domain by exploring the intersections of art, religion, performance, and ritual. It delves into the entangled histories that have shaped the current landscape of liturgical dance, highlighting the contributions of dance practitioners, religious scholars, theologians, and conciliar movements. These intertwined narratives reveal the complex factors that have led to the present situation, where liturgical dance is clogged from further development within the Roman Catholic Church and from reaching its full potential. The central problem of liturgical dance lies in the tension between its embodied, often ecstatic expression and the structured, hierarchical nature of traditional liturgy. Through an analysis of the erotic and ecstatic nature of dance and the para-sacerdotal role of the liturgical dancer, the paper uncovers the multifaceted nature of liturgical dance and its potential as a research practice to challenge existing theological frameworks. Theologians are called to mediate between artistic, academic, and religious communities to turn the problem of liturgical dance into a unique and innovative chance for radical renewal. To foster these innovative approaches and expand the boundaries of liturgical dance, the paper emphasizes the need for artistic laboratories. These laboratories can serve as spaces for dialogue and collaboration between theologians, dance scholars, and practitioners, paving the way for a new and promising research field of liturgical dance theology.
Keywords: dance history; Embodiment; Art and religion; liturgical dance; Liturgical Theology